Intermediate financial accounting 2016 : part 1A : based on Philippine financial reporting standards (PFRSs) - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2016)
"This book is designed to provide an invaluable learning material for accounting students and CPA candidates. Practicing accountants may also find this book a useful reference. It discusses and illustrates provisions of current financial reporting reporting standards in a clear and easy-to-read manner. Practical insights on how the standards are applied in actual practice are provided as well."
Includes appendix and references.
Keywords: Financial accounting